Evaluation of "How To Be A Good Mentoring Training” Effectiveness for Peer Mentor - Andhika Alexander Repi (Guidena)
"Kakak Pendamping, Support Class Program" is a term for peer mentor of Faculty Psychology WM University program. The mentor needs to be equipped with the knowledge, skills, and attitudes of becoming good mentors through training programs called "How To Be a Good Mentor" training. But, this program hasn’t evaluated whether the training is effective or not. If a training program is not assessed, it will cause several losses for both mentors and the organization. This study aims to identify the effectiveness of the training "How To Be a Good Mentor.” The method used is mix-method and involves all stakeholders in the UKWMS Psychology Faculty, namely staff, students, and Mentors. The results of the study found that "How To Be a Good Mentor" training has not been effective because it does not go through the ideal design stage of training. Without any needs analysis program, and the absence of a training evaluation program, as an action plan due to ineffectiveness of the training that has been held. A training module will be redesigned to develop a training module, "Creating a Full Heart Mentor." This training aims to improve the knowledge, skills, and attitudes of the Mentors. Evaluation of the "Creating a Full Heart Mentor" training is useful in evaluating the results of assessments showing the satisfaction of Mentor to the training process, and improving learning after obtaining training materials. The training on "Creating a Full Heart Mentor" produces needs analysis data used as a further development program for Mentors.